Characteristics of children’s toothpaste available on the market in the sertão paraibano (Research, Society and Development, 2022)
The present study aims to evaluate the characteristics of children's toothpastes accessible in the market of the hinterland of Paraíba, city of Patos, Paraíba, according to their commercial representation, availability and prices. The study was carried out by obtaining the toothpastes in commercial establishments of national representation in the city of Patos, and subsequent analysis of the packaging. Thus, 22 commercial brands of children's toothpastes from 10 manufacturers were found, 15 (68.18%) with fluoride and 7 (31.82%) without fluoride. In analysis, it was observed that of the fluoride toothpastes, with the exception of one, all had concentrations above 1000 ppm of fluoride. Prices ranged from BRL 2.25 to BRL 25.90. All were in the form of a gel, most with attractive flavors for children (90.90%) and colored (63.64%). More than half provided guidance on age and recommended keeping it out of the reach of children. Therefore, it can be concluded that there is a wide range of children's toothpastes available in different brands, compositions and prices for commercialization, with the majority being fluoridated and those with higher prices being non-fluoridated. The toothpastes are in the form of a gel and have advertising appeal to attract children in order to encourage consumption and there is no standardization of instructions on the packaging.